Symulacja jako narzędzie usprawniania zarządzania przedsiębiorstwem - Waćkowski, Kazimierz (Wydział Prawa i Administracji UAM, 1983)
The article includes: methodological remarks on simulation of the compound industrial systems, classifications of the operating systems most frequent in the machine industry, methodology of computer simulational experiments on those systems and multiple criterion analysis of their performance, reflections on integrating optimalizational models with segmental informatic systems for enterprise managing purposes, conception of a dialogue simulational system for the cited above needs. The problems are illustrated with model constructions and simulational calculations worked out on the basis of selected enterprises of Polish and the U.S.S.R.. machine industries. The author advises the economists to increase their interest in the dialogue experiments "man — machine" on real production system models in order to: discover their bottle-necks and organizational shortcomings, describe directions, of the system developement, analyse its previous functioning, improve management decision making and eliminate the direct experimenting on economic systems
Simulation as a technique improving the enterprise managing